'For a while out of orbit': listening to what unaccompanied asylum-seeking/refugee children in the UK say about their rights and experiences in private foster care. (December 2014) - Connolly, Helen
There is little in the existing refugee or child welfare literature on the circumstances and needs of unaccompanied asylum-seeking and refugee children living in private foster care in the UK. This article reports on what these young people themselves have to say about their experiences of such placements. Their stories have been extrapolated from the findings of a narrative-based research project with 29 unaccompanied asylum-seeking children that explored the ways in which they perceived and experienced the rights of the United Nations Convention on the Rights of the Child (UNCRC, 1989). The findings suggest the existence of a negative relationship between these rights and systems of monitoring and protection in the UK, and the vulnerability of unaccompanied children in private foster care to neglect, material hardship, abuse and exploitation.